Influence of climatic factors on the spittlebug population - Melo, Luiz Antônio Silveira; Silveira Neto, Sinval; Villa Nova, Nilson Augusto; Reis, Paulo Rebelles (Pesquisa Agropecuaria Brasileira, 2014)
This work was carried out in a pasture of Brachiaria decumbens Stapf to study the influence of climate and rainfall on the population of spittlebug (Homoptera - Cercopidae). Sampling of spittlebugs was made at two-week intervals during three years. The number of nymphs was counted on randomized areas of one square meter and the adult insects were collected with sweeping nets. Deois flavopicta Stal was the commonest spittlebug that occurred at the rate of 91.2%. The highest frequences of the spittlebugs took place as from September/October to April/May. The nymphal peak occurred by the end of October, and the population peak of adults occurred evenly during the period time of the present study. Eleven climate factors studied singly and in combination were considered in relation to the spittlebug population of adult spittlebug. There was statistical significancy between all correlations except for rainfall and population. Means to know the favorable condition for spittlebug population development were also provided. Combined factors Relative Humidity x Temperature influenced greatly on the spittlebug population, as well as the hydric balance in the soil.